(untitled) (Asian Journal of Medical and Biological Research, 2016)
Drinking water from natural sources in coastal region of Bangladesh has been contaminated by varying degrees of salinity which have detrimental effects on the health. Pregnancy itself is a crucial time for women and the salinity increases its vulnerability regarding the raising of blood pressure. The study was conducted to evaluate the effect of saline water intake on the health status of pregnant women at Barguna and Patuakhali districts, Bangladesh. Sodium (Na) concentration in urine samples was analyzed and corresponding blood pressure was taken in the diagnostic laboratory. Descriptive statistical analysis showed that Na concentration, systolic and diastolic pressure (BP) was the highest in 2nd trimester followed by 3rd trimester and 1st trimester. Water intake and urine production were the highest in 3rd trimester and increased with age. Na concentration, systolic and diastolic pressure (bp) was the highest in 3rd parity followed by 2nd parity. Water intake and urine production did not very among parities. Correlation matrix express that sodium concentration has the significant association with the age and the highly significant association with systolic and diastolic blood pressure. In Logistic Regression Model, odds ratio (OR) estimate showed that women with systolic bp?120 had 1.109 times greater sodium concentration than with systolic blood pressure of <120 and, with diastolic bp ? 80 contain 1.064 times greater sodium concentration than with diastolic blood pressure of < 80. Asian J. Med. Biol. Res. March 2016, 2(1): 55-61